Establishment of KUB as Alternative to Economic Independence of Pedak Society, Srandakan, Bantul - Muhammad Zakiy; Rozikan (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
The economic independence of rural communities depends on the ability of the community to run the businesses owned by it's self. One of the businesses that can be developed by the village community is the development of culinary snacks which are the daily needs of the community. This empowering program aims to increase the economic independence of the people of the Pedak in the village of Trimurti, Srandakan District, Bantul Regency through the establishment of Kelompok Usaha Bersama (KUB). The output of this program is the establishment of KUB which is engaged in culinary snacks which are sold in several places such as cake shops and cake bazaars during of Ramadan. In addition, the resulting cake products will also be tried to be marketed in the tourist area of Bantul beach and tourists who pass the main Bantul-Kulonprogo road. From the formation of the KUB it is hoped that the community can be empowered so that the economic independence of the community can increase their income.  This program is implemented because the Pedak area has potential in product marketing and high demand for snacks. For the success of this program, training in food management, packaging according to standards and structured marketing and organizational training has been carried out.